PENGARUH PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA TERHADAP KINERJA KONTEKSTUAL: PERASAAN POSITIF SEBAGAI PEMEDIASI PADA PEGAWAI RSUD KAB. ACEH BESAR - Husna Jm Fortuna; Yurnalis Yurnalis (Departemen Manajemen, 2020)
This study aims to measure the effect of Human Resources Management Practices on Contextual Performance: Positive Emotions as a mediating variable in Employees of RSUD Kab. Aceh Besar. The sample used in this study was employees of RSUD Kab. Aceh Besar, which amounted to 175 respondents. Data collection equipment used in this study is a questionnaire. The sampling technique used is Probability sampling Simple Random Sampling. Regression analysis is used as an analytical method to determine the effect of all the variables involved. Based on the results of the regression analysis, indicating that the Human Resource Management Practice positively Contextual Performance, Human Resource Management Practice positively Positive Emotions, Positive Emotions positively Contextual Performance, and Positive Emotions mediate the relationship between Human Resource Management Practice and Contextual performance.